Design of Bus Material on Amphibious Bus as an Alternative Mass Transportation to Overcome Traffic Congestion in Jakarta Metropolitan - Aprilya, Sonia; Aritonang, Sovian; Coutsar, Ardan Nagra (Peneliti.net, 2024)
According to the Central Statistics Agency of the DKI Jakarta Province, the number of motor vehicles in DKI Jakarta in 2021 reached 21,758,695 units, with motorcycles dominating at 16 million. With a land area of 64.5 km2, traffic congestion is inevitable. Because of this condition, this study proposes a mass transportation means that can pass through land and water, namely the Amphibious Bus. When in water, the most important part of a ship is the hull. Some requirements that must be met to design a ship's hull include being lightweight, corrosion-resistant, fire-resistant, and safe and comfortable for passengers. Several materials are considered as materials for amphibious buses, namely low carbon steel, alumunium, Fiberglass Reinforced Plastic, Stainless Steel. From the AHP comparison, low carbon steel and FRP have advantages in compressive strength, tensile strength, and bending strength compared to other materials. Meanwhile, aluminum has the advantage of corrosion resistance compared to other materials.